The Role of Carbapenems in the Management of Diabetic Wounds (Medical Forum Monthly, 2024)
Objective: To study the role of Carbapenems in the Management of Diabetic Wounds.Study Design: Prospective StudyPlace and Duration of Study: This study was conducted at the Idris Teaching Hospital Sialkot from January 2014- Nov 2017.Materials and Methods: To study the role of Carbapenems in the Management of Diabetic Wounds. One hundred patients of diabetic wounds were included in this prospective study during January 2014- Nov 2017 at Idris Teaching Hospital Sialkot. Carbapenems antibiotic one gram twice daily was given to all patients in this study. The performa was designed to record age, gender, duration of treatment, grades of the wounds & area of the body involved in diabetic wounds. Informed consent of all the patients was considered before treatment and permission of ethical committee of the institute was also obtained.Results: The diabetic wounds were more common in female 63 (63%) as compare to male 37(37%) as shown in table no.1. The common age range was 50-60 years 35 (35%) cases in female and 20 (20%) cases in male as shown in table no.1. The incidence of diabetic wounds of foot, legs, back, and hands was 86%, 3%, 5% and 6% respectively as shown table no.2. It showed that the foot was most common area involved in diabetic wounds 86 cases (86%). The incidence was in different grades of the wounds (I-V), 20 (20%), 30 (30%), 20 ( 20%), 15 (15%) & 15 (15%) respectively as shown in table no. 03. It showed that the incidence of grade II wounds was maximum 30 (30%). In grades of wounds from I-V, the duration was 3-7 days, 8-15 days, 16-30 days, 31-45 days, 46-60 days respectively as shown in table no.03. Conclusion: It showed that wounds of the grade 2 have maximum incidence 30 (30%) as compared to other grade of the wounds.